Exploring the knowledge and attitude of public about mental health problems: A pilot intervention for effective mental health promotion - Meena Kolar Sridara Murthy; Aruna Rose Mary Kapanee; Geetha Desai; Santosh Kumar Chaturvedi (Wolters Kluwer Medknow Publications, 2019)
CONTEXT: The knowledge about mental health problems among the general public is comparatively quite low. The pilot study was conducted with an aim to increase the knowledge of the day-to-day mental health problems which people can have among the mass. AIMS: The aims of this study are (1) to assess the knowledge and attitude about mental health problems of the selected sample and (2) to build the capacity in providing first aid for mental health to the selected sample through training. SETTINGS AND DESIGN: A cross-sectional study was used in assessing the knowledge and skills of the participants of the first aid for mental health problems. It was conducted in the institute itself. SUBJECTS AND METHODS: A total of 89 participants were taken to participate in the cross-sectional study. Using a semi-structured self-administered questionnaire, a brief training, and a feedback form, capacity building for first aid for mental health problems was provided. STATISTICAL ANALYSIS USED: The questionnaires were analyzed using descriptive statistics. RESULTS: The capacity building program for first aid for mental health problems appears to be effective in improving the knowledge and attitude with regard to the mental health problems. The findings from the program indicated lack of knowledge in understanding of mental health, knowledge of causation, and treatment of mental health problems. Feedback of the training program indicated that it improved the ability of the participants in recognizing persons undergoing mental health problems and brought about a change in their beliefs about mental health, attitudes, and need for prompt referral. CONCLUSIONS: The program was successful in increasing the confidence of the participants in providing help to someone with a mental health problem and referring to appropriate mental health professional. This shows that there is an immediate need for empowering general public with knowledge and skills to provide support to people with mental health problems.